2010
DOI: 10.1007/s10519-010-9393-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Environmental Etiology of Disregard for Rules

Abstract: Disregard for rules, a key component of oppositional defiant and conduct disorders, is stable during early childhood. This study investigates for the first time the relative importance of genetic and environmental factors underlying this early developmental stability. Maternal reports of child disregard for rules were obtained at four time points from 20 to 64 months of age in a population-based twin sample (N = 597 twin pairs, including 238 monozygotic and 359 dizygotic pairs). Structural equation modeling wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 26 publications
4
18
0
Order By: Relevance
“…We have documented variations in the genetic and environmental contributions to different forms and functions of aggressive behaviors, such as reactive versus proactive versus social aggression at school entry (Brendgen et al, 2005(Brendgen et al, , 2006, as well as to physical aggression, language, and their association at 18 months of age (Dionne et al, 2003). We also showed that the stability, but not the episodic manifestations of disregard for rules, a central component of early opposition, has a significant genetic component (Petitclerc et al, 2011). In contrast, cognitive school readiness before school entry was found more strongly accounted for by environmental factors shared and uniquely experienced by children of the same family than by genetic predisposition.…”
Section: Scientific Contributionmentioning
confidence: 87%
“…We have documented variations in the genetic and environmental contributions to different forms and functions of aggressive behaviors, such as reactive versus proactive versus social aggression at school entry (Brendgen et al, 2005(Brendgen et al, , 2006, as well as to physical aggression, language, and their association at 18 months of age (Dionne et al, 2003). We also showed that the stability, but not the episodic manifestations of disregard for rules, a central component of early opposition, has a significant genetic component (Petitclerc et al, 2011). In contrast, cognitive school readiness before school entry was found more strongly accounted for by environmental factors shared and uniquely experienced by children of the same family than by genetic predisposition.…”
Section: Scientific Contributionmentioning
confidence: 87%
“…These items were included in Canada's National Longitudinal Survey of Children and Youth (Statistics Canada, 1995), and originate from the Child Behavior Checklist/2-3 (Achenbach, 1992). The scale has shown good psychometric properties and stability between ages 17 and 41 months , and between 29 and 74 months (Petitclerc et al 2009), as well as a substantial genetic basis (Petitclerc et al 2011). All DB items were rated on a 3-point scale: 0/never; 1/sometimes; and 2/often.…”
Section: Disruptive Behaviors In the Preschool Yearsmentioning
confidence: 99%
“…A few longitudinal twin studies have provided evidence that stability in certain traits and behavior patterns (activity, affect/extraversion, behavioural inhibition, disregard for rules, physical aggression), is substantially accounted for by genetic factors [29,30,33,34], while at the same time indicating that the genetic effects are developmentally dynamic, i.e. varying over time, with previously inactive genes coming online (genetic innovation; see [33, 34, 35]).…”
Section: Introductionmentioning
confidence: 99%
“…varying over time, with previously inactive genes coming online (genetic innovation; see [33, 34, 35]). Additionally, environment factors appeared to drive some of the change in temperament during this time [29,34,36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation